Policy Implementation in Realizing the Effectiveness of Disaster Management - Iskandar, Jusman; Salamah, Ummu; Patonah, Nonah (International Journal of Engineering and Technology, 2018)
A natural disaster is an undesirable event and it can happen anytime. The government should be present to decrease the consequences of natural disaster, so it is necessary to make public policy and coordination between government agencies to handle a natural disaster. The purpose of this study is to analyze the influence of the implementation of disaster management policy towards coordination between regional work units in realizing the effectiveness of disaster management. The research methodology used is a quantitative method with path analysis technique. The research was conducted in Regional Disaster Relief Agency of Garut District (Indonesia) with 73 respondents. The results showed that the disaster management policy has a positive and significant effect on the coordination between regional work units in realizing the effectiveness of disaster management. The research finding showed that the good implementation of policy can be performed through improving coordination between Regional Work Units to realize the effectiveness of disaster management.Â Â